Análisis epidemiológico de onicomicosis diagnosticada por laboratorio en pacientes menores de 15 años - Palma D., Carlos; Zemelman D., Viviana; Stevens G., Jonathan; Araníbar D., Ligia; Zapata M., Solange; Hernández V., Alicia (Revista Hospital Clínico Universidad de Chile, 2017)
Onychomicosis was considered uncommon in children. During recent years an increase in its frequency has been reported in children worldwide. This survey was carried out to estimate the frequency of causal agents of fungal nail infections in children and adolescents (0-15 years of age) during the period 2006-2016 in the Skin Laboratory of Clinical Hospital, University of Chile. It was a descriptive, retrospective analysis of all positive culture of children nails. A total of 1626 culture was analyzed. Cultures were positive in 417 cases (25,6%). Average age of patients with positive culture was 9,37 ages. Of the total positive culture, 42,9% was females and 57,1% was males. Toenails were more affected (90,6%) than finger nails. Trichophyton rubrum (66,9%), was the predominant pathogen isolated followed by Candida spp (26,1%) Trichophyton rubrum + Candida spp (3,8%) Trichophyton mentagrophytes (2,6%) and Trichophyton rubrum + Trichophyton mentagrophytes (0,5%). Fungal fingernail infection by Candida spp. was the most common (66,7%) and Trichophyton rubrum was the most common in toenail (70,6%). We found a decrease of Candida spp. with age. The results of our study show that onycomichosis in children and adolescents is not exceptional and should be considered in the differential diagnosis of nail plate disorder in children.